Rational understanding from explanation to knowledge - Belkoniene, Miloud 1988- (Routledge, 2023)
"This book develops a novel account of the connections between justification, understanding and knowledge. It lays the foundation for a more systematic and interconnected treatment of these central notions in epistemology. The author's key move is to show first that a specific conception of doxastic justification constitutes our best point of entry into questions pertaining to a subject's ability to secure understanding of reality. Second, that the traditional order of analysis when it comes to the connection between understanding and knowledge should be reversed: knowledge itself is best conceived of in terms of a specific type of understanding. Rational Understanding will appeal to scholars and advanced students working in epistemology and philosophy of science"--
Keywords: Knowledge, Theory of; Comprehension; Théorie de la connaissance; Compréhension; epistemology; Comprehension (Theory of knowledge); Explanation; Justification (Theory of knowledge)